The Factors Affect Life Expectancy at Birth In Middle East and North Africa (MENA) Region During the Period (2000-2016) - Hashem, Aziza (The Arab Journal of Administration, 2021)
By the data of 19 countries in middle east and north Africa (MENA) region during the period (2000-2016) we analyze and investigate a number of economic, social and environmental factors that affect life expectancy at birth to know which factors will influence life expectancy at birth in MENA region. The study tested the validity of the assumption that economic, social and environmental factors significantly affect the life expectancy at birth in the countries of the MENA region. Therefore, the study uses ewiews10 by panel data and small squares method to determine the relation between life expectancy at birth and factors affect it. As the fixed impact model was used to estimate the information based on tests to compare between different models. The study shows that some factors have a significant effect on the life expectancy at birth and others do not have a significant affect in MENA countries during the period (2000-2016). Factors have a positive significant affect are: compulsory education years, percentage of people using basic drinking water services to total population, percentage of urban population to total population, immunation DPT (% of children ages12-23 months) and the percentage of government expenditure on education of total government expenditure. While factors have a negative significant effect on life expectancy at birth are: age dependency as a percentage of working age population and the percentage of people using basic sanitation services to total population. On the other hand, factors do not have significant effects on life expectancy at birth are CO2 emission (metric tons per capita), total fertility rate, GDP per capita ppp and current health expenditure per capita ppp. Finally, the study recommended that the government should care about factors that have a positive significant effect on life expectancy at birth throw different, polices as increasing government investment in infrastructure projects in drinking water, increasing immunation for children and increasing government expenditure in health sector especially in rural and far areas.